2020
DOI: 10.21203/rs.2.21278/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determining the association between fibromyalgia, the gut microbiome and its biomarkers: A systematic review

Abstract: Background The association between fibromyalgia and irritable bowel syndrome is well-established. Alterations in the composition and diversity of the gut microbiome in irritable bowel syndrome have been reported, however, this association is poorly understood in fibromyalgia. Our aim was to summarise the research reporting on the gastrointestinal microbiome and its biomarkers in people with fibromyalgia.Methods A systematic review of published original research reporting on the gastrointestinal microbiota and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
1
6
0
3
Order By: Relevance
“…With these considerations in, it is reasonable to suspect that FMS-related alterations in the fecal microbiome may be obscured by the influence which psychopathology, medication and/or diet have on the microbiome. This contention is in line with the conclusion of Erdrich et al [55] that the relationship between the gut microbiome and the pathophysiology of FMS remains a largely underexplored area.…”
Section: Plos Onesupporting
confidence: 88%
“…With these considerations in, it is reasonable to suspect that FMS-related alterations in the fecal microbiome may be obscured by the influence which psychopathology, medication and/or diet have on the microbiome. This contention is in line with the conclusion of Erdrich et al [55] that the relationship between the gut microbiome and the pathophysiology of FMS remains a largely underexplored area.…”
Section: Plos Onesupporting
confidence: 88%
“…However, it is still unclear whether these changes have a pathogenetic role in FM, and if the manipulation of the microbiome could impact on FM symptoms. A systematic review on this topic has been made by Erdrich et al (27), who identified five broad areas of research with papers reporting on Helicobacter pylori, other gut bacterial markers and metabolomics, including intestinal permeability and small intestinal bacterial overgrowth. Despite the limitations of the included studies, associations emerged between composition and metabolism of the gastrointestinal microbiota and FM, as well as preliminary findings of the effectiveness of gastrointestinal microbiome-targeted interventions in improving clinical symptoms and/or laboratory measures related to FM.…”
Section: Clinical and Experimental Rheumatology 2021mentioning
confidence: 99%
“…A consistência das fezes identificada pela escala de Bristol, revela a predominância dos tipos 1, 2 e 3 conforme pode ser observado no gráfico 1, sendo a constipação classificada pelo tipo 1 em 28,17% (n=20) e tipo 2 em 25,35% (n=18) da amostra, indicando ser essa uma condição prevalente em mulheres com fibromialgia (ERDRICH et al, 2020b).…”
Section: Resultsunclassified
“…A constipação causa desconfortos e alterações no funcionamento intestinal, esvaziamento incompleto, esforço excessivo, bem como fezes pequenas e duras propiciando o surgimento de inchaço, gases etc. Quando não tratada corretamente podem aparecer complicações como hemorroida, uma vez que o tratamento é desafiador e por vezes faz-se necessário a associação de terapias multicomponentes bem como mudanças no estilo de vida, dependendo da etiologia (ERDRICH et al, 2020b;FANG et al, 2021). O consumo alimentar encontrado na amostra, revelou valores percentuais e em gramas adequados com as referências estabelecidas pela DRIS (2014) para a gordura total, assim como valor compatível da média proteica percentual de acordo com as recomendações estabelecidas.…”
Section: Resultsunclassified